Modal Auxiliary Verbs in The Jakarta Post Op-Ed Articles by Indonesian and Non-Indonesian Writers - Rahmawati, Aulia Nur; Hardjanto, Tofan Dwi (Universitas Gadjah Mada, 2025)
This study was aimed at finding the meaning, similarities, and differences of the use of modal auxiliary verbs in editorial articles from an Indonesian newspaper, The Jakarta Post, regarding the writers’ various linguistic backgrounds. The data were collected from 20 editorial articles written by Indonesian and non-Indonesian writers using corpus linguistics software #Lancsbox v. 6.0, which found 286 instances of eight modal auxiliary verbs. The most commonly employed modal auxiliary verbs by both Indonesian and non-Indonesian writers are can, will, should, may, would, could, must, and might, respectively. Biber et al.’s (1999) classification of deontic and epistemic meanings was used to find the meaning of the modal auxiliary verbs. The results of this study show that Indonesian and non-Indonesian writers used modal auxiliary verbs significantly differently, suggesting that linguistic and cultural background might affect the use of modal auxiliary verbs, especially in newspaper editorial articles. Furthermore, the results also show that both groups of writers used more modal auxiliary verbs with epistemic meaning rather than with deontic meaning, indicating their commitment to the truth of their argument.